Congenital heart disease in adults: Quantitative and qualitative evaluation of IR FLASH and IR SSFP MRA techniques using a blood pool contrast agent in the steady state and comparison to first pass MRA. Issue 10 (October 2015) - Febbo, Jennifer A.; Galizia, Mauricio S.; Murphy, Ian G.; Popescu, Andrada; Bi, Xiaoming; Turin, Alexander; Collins, Jeremy; Markl, Michael; Edelman, Robert R.; Carr, James C.
Highlights: IR-SSFP shows best results in CHD in adults when blood pool agents are administered. Higher image quality and fewer artefacts observed. Higher diagnostic confidence. Seven out of twenty-three cases had congenital defects seen using IR-SSFP that were not observed with FP-MRA. Abstract: Objectives: To evaluate magnetic resonance angiography sequences during the contrast steady-state (SS-MRA) using inversion recovery (IR) with fast low-angle shot (IR-FLASH) or steady-state free precession (IR-SSFP) read-outs, following the injection of a blood-pool contrast agent, and compare them to first-pass MR angiography (FP-MRA) in adults with congenital heart disease (CHD). Materials and methods: Twenty-three adult patients with CHD who underwent both SS-MRA and FP-MRA using a 1.5-T scanner were retrospectively identified. Signal-to-noise and contrast-to-noise ratios were obtained at eight locations within the aorta and pulmonary vessels.. Image quality and the presence of artifacts were subjectively assessed by two radiologists. The presence of pathology was noted and given a confidence score. Results: There was no difference in vessel dimensions among the sequences. IR-SSFP showed better image quality and fewer artifacts than IR-FLASH and FP-MRA. Confidence scores were significantly higher for SS-MRA compared to FP-MRA. Seven cases (30.4%) had findings detected at SS-MRA that were not detected at FP-MRA, and 2 cases (8.7%) had findings detected by IR-SSFP only. Conclusion: SS-MRA of the thoracic vasculature using a blood pool contrast agent offers superior image quality and reveals more abnormalities compared to standard FP-MRA in adults with CHD, and it is best achieved with an IR-SSFP sequence. These sequences could lead to increased detection rates of abnormalities and provide a simpler protocol image acquisition.